History of Restoration in Iran: Origins and Developments from 1900 to 1978 - Zargaran, Pooya <1980> (Alma Mater Studiorum - Università di Bologna, 2014)
This thesis tends to study the origins and developments of the restoration in Iran from its very first moments till the Islamic revolution of 1978. The thesis is its first study of its kind. While almost all recent occidental ideologies regarding the thematic of restoration and conservation of historic monuments are translated and published in Iran, very little efforts have been done regarding the study of the origins of the formation of restoration in the country. The diversity of Iranian contexts, multiplicity of the intervening factors and other factors characterized a different background for the raise and developments of restoration in the country; in the thesis the influencing and characterizing factors in the formation and development of restoration in Iran will be defined and studied in detail with relative examples; due to the complexity of the Iranian context and in order to consider all influencing and characterizing factors the thesis, parallel to have formation and development of restoration, as the main scope of the research, the developments influencing factors will be confronted with necessary flashbacks to the main theme, when and where necessary. A great care will be given to the period of the activity of the restoration experts of IsMEO which is thesis will be called as the period of the introduction of the modern principles of restoration into Iranian context; the fundamental ideologies, practical and theoretical principles of IsMEO will be identified and studied in details; important case of studies of the restoration of IsMEO will be analyzed in details and the innovative aspect of the presence of Italian experts of IsMEO will be revealed.